Pediatric focal segmental glomerulosclerosis: favorable transplantation outcome with plasma exchange - Fatina I. Fadel; Hafez M. Bazaraa; Mohamed A. Abdel Mawla; Doaa M. Salah (BMC, 2021)
Abstract Background Although kidney transplantation (KTX) is the treatment of choice for pediatric end stage kidney disease (ESKD); concerns for recurrence in cases of focal segmental glomerulosclerosis (FSGS) are still present. This study aimed to investigate the outcome of KTX in children with ESKD secondary to FSGS, with implementation of preemptive perioperative plasma exchange (PE) for non-genetically proven patients. Methods Forty FSGS pediatric kidney transplant recipients were studied. Of them: 12 patients (30%) had genetically proven NPHS2 mutations/familial and 28 (70%) were sporadic FSGS patients. All sporadic patients electively received 6 perioperative PE sessions. Patients with recurrence of proteinuria (n = 13; including 3 patients with genetic/familial and 10 patients with sporadic FSGS) were managed with PE and Rituximab (RTX). Kaplan-Meier curves were used to analyze graft and recurrence free survival data. Results The mean follow-up duration after KTX was 3.8 ± 2.86 years. Recurrence of proteinuria was encountered early postoperative in 11 patients (27.5%) and late (1.6 and 2.9 years after KTX) in 2 patients (5%). All patients with early recurrence achieved complete remission, while patients with late recurrence developed graft failure. Current serum creatinine and proteinuria levels were not different in patients received PE (n = 31) and patients did not PE (n = 9) (p = 0.308 and 0.287 respectively). Current serum creatinine and proteinuria levels in sporadic patients (n = 28) after prophylactic perioperative PE were not different from those of genetic/ familial patients (n = 12) (p = 0.303 and 0.144 respectively). Proteinuria was less in patients underwent native nephrectomy than others immediately postoperative and at assessment (p = 0.002 & 0.0031 respectively). One-year graft and patient survival was 93.8% with a mean 1-year serum creatinine of 0.67 ± 0.25 mg/dl. Three graft losses (7.5%) were due to chronic rejection 3.3, 3.75 and 4.17 years after KTX and 2 patients' mortality (5%) occurred early postoperative (first 2 weeks). Conclusion FSGS transplanted children have favorable outcomes with perioperative PE for non-genetically proven cases. Early recurrence after KTX can be successfully managed with PE and RTX.